Investigation of deterioration in corroding reinforced concrete beams using active and passive techniques - Sharma, A.; Sharma, S.; Sharma, S.; Mukherjee, Abhijit (Elsevier BV, 2018)
© 2017 Elsevier Ltd Electro-chemical techniques that are routinely used in monitoring corrosion of reinforced concrete give an overall estimate of corrosion. Non-destructive techniques that are able to estimate the residual strength of corroding structures would help a great deal in strategizing post-corrosion maintenance. This paper explores two non-destructive techniques based on wave propagation for estimating residual strength of corroding reinforcement in concrete. The specimens undergoing corrosion were simultaneously monitored by acoustic emission (passive) and ultrasonic guided wave (active) techniques. The specimens were instrumented with AE sensors to record acoustic activities inside the specimens during corrosion. Simultaneously, the bars are also monitored by propagating ultrasonic waves through the bars. Active and passive monitoring results are correlated with already established electrochemical techniques to determine the relative efficacies of the NDT technologies. At the end of the exposure, the residual strength of the bars has been determined by tensile testing.